2019
DOI: 10.1063/1.5083182
|View full text |Cite
|
Sign up to set email alerts
|

The statistical data on microdischarges of the surface dielectric barrier discharge unit based on aluminum nitride barrier

Abstract: A new mathematical processing method for current signals from surface dielectric barrier discharge in conditions of high noise is suggested. This technique is based on the analysis of isolated microdischarge parameters: charge transfer, impulse duration, and voltage/phase, followed by statistical analysis. Research was carried out on surface dielectric barrier discharge units with a copper thin corona electrode on a 1 mm aluminum nitride barrier. Four modes with the corresponding rms-voltages of 1.8, 2.0, 2.2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…The finding associated with long pulses formation is the imbalance of the total charge carried by pulses in positive and negative half-periods. The charge imbalance in such measurements was previously obtained in a similar electrode arrangement [25]. The part of the charge in negative HP can be carried by a continuous current component; thus a glow mode of the discharge can coexist with the pulses.…”
Section: Copper Electrodementioning
confidence: 68%
See 1 more Smart Citation
“…The finding associated with long pulses formation is the imbalance of the total charge carried by pulses in positive and negative half-periods. The charge imbalance in such measurements was previously obtained in a similar electrode arrangement [25]. The part of the charge in negative HP can be carried by a continuous current component; thus a glow mode of the discharge can coexist with the pulses.…”
Section: Copper Electrodementioning
confidence: 68%
“…The study of statistics of current pulses in atmospheric pressure discharges is a fairly standard approach, which allows a deeper understanding of the processes of self-organization of MDs. In [22][23][24][25] statistics of MDs for a barrier discharge in volume, coplanar, and surface configurations are presented. It was demonstrated that the presence of remnant charges on the dielectric surface leads to an increase in the transferred charge in subsequent MD generations [26,27].…”
Section: Microdischarges In Surface Barrier Dischargementioning
confidence: 99%
“…[31] Due to the great difference in mobility between electrons and positive ions, electrons drift toward and enter the needle anode in the needle-tube discharge, depositing positive ions in the discharge channel and on the inner surface of the tube. [32] With the proceeding of the needle-tube discharge, more and more positive ions are accumulated, which can enhance the electric field in the right region of the needle. As a result, the electric field grows with time, inducing a positive streamer when it reaches a threshold.…”
Section: Resultsmentioning
confidence: 99%
“…Разряд существует в виде большого числа кратковременных микроразрядов, отличающихся для положительной и отрицательной полуволны. При питании разряда гармоническим напряжением микроразряды группируются по питающим полуволнам, создавая паузу в горении разряда [6]. Это обеспечивает импульсный режим воздействия без дополнительных ис-полнительных средств.…”
Section: Introductionunclassified